Effect of Anemia on Birth weight Among Pregnant Women Attending ANC Clinic at Public Hospitals of Sidama Region, Ethiopia, 2022: A Prospective Cohort Study Protocol - Tegegne, Kaleab Tesfaye; Assefa, Abiyu Ayalew; Zenebe, Andualem; Bagajjo, Wosenyeleh Semeon; Rike, Musie; Abebe, Alelign Tadele; Assefa, Sintayehu (International Journal For Research In Health Sciences And Nursing, 2021)
Background: Anemia is the main cause of morbidity and mortality among pregnant women in developing countries with maternal and fetal consequences, which leads to premature births, low birth weight, fetal cognitive impairment and death. Objective: To establish association between anemia and birth weight among pregnant women attending ANC clinic at public hospitals of Sidama region, Ethiopia, 2022.. Methods and materials: a prospective cohort study design will be conducted from March 1, 2022 to November 30, 2022 in public hospitals of Sidama region. A total of 12 Midwives and 6 supervisors will be involved in the data collection process. Exposed (pregnant women having anemia ) and non-exposed (pregnant women not having anemia ) will be selected by using simple random sampling technique from the prior three months ANC register of each selected public hospital The data will be entered into Epidata software and exported to SPSS software for windows version 23 for analysis. Descriptive statistics will be computed and both bivariable and multivariable logistic regression will be employed to assess effect of anemia on birth weight among pregnant women. The output will be presented using adjusted odds ratio (AOR) with the respective 95% confidence interval (CI).